A Case Series of Acute Methanol Poisoning from Northern Kerala - Shinto Francis T; Jyotish Nair R; Shiji PV; Shaan Mohamed; Geetha P and Sasidharan PK (Emergency Med, 2016)
Background: Methanol is a cheap, potent adulterant widely used in illicit liquor. There have been several episodes of mass methanol poisoning in our country with varying mortality and morbidity rates. Serious attempts to study the profile and common variables of such patients have not been attempted from Kerala. Aim: To study the clinical profile and prognostic factors in patients who were victims of the methanol poisoning admitted in a teaching hospital. Methodology: Twenty four cases of methanol poisoning from adulterated toddy admitted to Calicut Medical College Hospital in September 2010 during a single outbreak of a hooch tragedy were studied. Results: Out of total 24 admissions, 4 died and 4 developed permanent blindness. Of the 4 patients who died, 3 were brought in a critical condition, and succumbed to the toxic effects of methanol even before starting any form of treatment and the fourth died before receiving hemodialysis. Four patients with initial complete visual loss didnot regain vision even after correction of acidosis and hemodialysis. Fourteen patients who had blurring of vision and other symptoms completely improved after intensive alkalinisation therapy and hemodialysis. The latent period between the alleged consumption of adulterated toddy and development of symptoms was variable. Minimum fatal period was 10 hours and maximum was 2 days. All patients who were subjected to haemodialysis had short period of hospital stay. Conclusion: This observational study shows that all those patients who received prompt and early alkalinisation therapy, 10% ethanol infusion, folinic acid injections and hemodialysis had striking recovery, except those who had initial complete loss of vision. The blood pH value was found to have direct correlation with visual outcome. Poor nutritional status indicated by a low BMI was suspected to have a role in increased susceptibility to toxic effects of methanol, possibly suggesting coexisting folic acid and other multiple vitamin deficiencies in such patients.